Antituberculous activity of norfloxacin Mannich bases with isatin derivatives - Pandeya S.N.; Sriram D.; Yogeeswari P.; Ananthan S. (My University, 2025)
Mannich bases of norfloxacin were synthesized by reacting them with formaldehyde and several isatin derivatives. The compounds were evaluated in vitro against Mycobacterium tuberculosis H37Rv at 12.5 μg/ml in BACTEC 12B medium using the BACTEC radiometric system. Among the compounds tested, S-10 showed promising activity, with 100% inhibition at a concentration lower than 6.25 μg/ml. Copyright © 2001 S. Karger AG, Basel.